Penguatan dan Pengembangan Revitalisasi BUMDes sebagai Organisasi yang Berkelanjutan dalam Rangka Percepatan Ekonomi Desa - Wa Ode Zustina Muizu; Wafi Fu'adi; Irma Masyitoh; Febriani; Dara Sagita Triski (Universitas Serang Raya, 2024)
Sindangsuka Village has residents who run various businesses, such as animal husbandry, agriculture, and entrepreneurship. With the condition of Sindangsuka Village, which until now is experiencing water shortages, the business activities run by the village community are hampered and cannot be run optimally. The low population of productive age is a supporting factor for the lower number of business actors in the village. Since 2016, the BUMDes of Sindangsuka Village have been trying to develop their business units in order to improve the village economy, but they have not received full support from the residents. The Integrative KKN-PPM program was carried out in Sindangsuka Village from 11 July to 11 August 2023 with the aim of analyzing, identifying SWOT, formulating the best recommendations on BUMDes problems in the organizational sector. Training and mentoring is provided to BUMDes with the hope that BUMDes organizational values can be increased. Through this program, BUMDes can form an organizational roadmap, strengthen the functions of each part of its structure, and compile year-end reports.